The role of the exposure of education technology on learners' internet self-efficacy - Chen, Xiaoyuan (Transactions on Social Science, Education and Humanities Research, 2024)
The advancement of educational technology has undoubtedly had a influence on how teachers present learning materials and interact with students in the language teaching context over the last few decades. Despite the fact that many studies have been conducted in the field of educational technology, few of them have focused on the relationship between educational technology and internet self-efficacy. Based on social cognitive theory, which views learners as active agents who can not only affect but also be affected by environment, the purpose of this research is to evaluate how exposure to educational technology impacts learners' internet self-efficacy. Furthermore, this research explores how potential variables such as gender, grade, and discipline influence learners' internet self-efficacy. Seventy-one students from a Chinese vocational institute were asked to finish the College Students' Internet Learning Self-efficacy Questionnaire (Xie, 2011) and a questionnaire designed on the basis of the AECT committee's definition, and some participated in a semi-structured interview. The findings indicate that the relationship between exposure to educational technology and learners' internet self-efficacy has significantly facilitated our understanding of how to improve teaching and learning with educational technology. The implication of this study is that when incorporating educational technology into English teaching, teachers should consider the quantity, quality, and methods.